Соціальне підприємництво для інвалідів, як вектор європейського розвитку національної економіки - Гордєєва, Інна Олександрівна (Видавництво Львівської політехніки, Львів, Україна, 2015)
UKR: Дослідження містить аналіз шляхів створення соціального підприємництва для створення робочих місць для людей з інвалідністю: переваги та недоліки.

ENG: The research includes an analysis of the ways to establish social entrepreneurship aimed at creating job opportunities for people with disabilities: advantages and disadvantages.
Social Entrepreneurship for People with Disabilities as a Vector of European Development for the National Economy
І. Гордєєва: ORCID 0000-0002-2019-2527
Keywords: грантрайтинг; проектний менеджмент; грант-менеджер; соціальне підприємництво; люди з інвалідністю; grant writing; project management; grant manager; social entrepreneurship; people with disabilities; КУПББМ